1981
DOI: 10.1029/wr017i006p01676
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for estimating convective rain volume over an area

Abstract: Previous authors have reported significant correlations between the horizontal extent of convective showers or storms and the volume of rain they produce. This paper employs that idea to develop a simplified method for estimating convective rainfall by considering only the horizontal extent and duration of the precipitation. The present analysis is based on rain gage and radar data from an area in western North Dakota. A synoptic adjustment is applied to the radar rain volume estimates. A quantity called the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 11 publications
1
19
3
Order By: Relevance
“…They found that the total rainfall produced by individual storms can also be estimated simply by considering only the horizontal extent and the duration of radar-observed precipitation. Doneaud et al (1981), however, did not present a convincing explanation for the high correlations found. Later, Atlas et al (1990) recovered their approach and presented a unified theory for both the estimation of the total rainfall of an individual storm and for the average instantaneous rain rate from a multiplicity of such storms.…”
Section: Introductioncontrasting
confidence: 73%
See 2 more Smart Citations
“…They found that the total rainfall produced by individual storms can also be estimated simply by considering only the horizontal extent and the duration of radar-observed precipitation. Doneaud et al (1981), however, did not present a convincing explanation for the high correlations found. Later, Atlas et al (1990) recovered their approach and presented a unified theory for both the estimation of the total rainfall of an individual storm and for the average instantaneous rain rate from a multiplicity of such storms.…”
Section: Introductioncontrasting
confidence: 73%
“…where P(R) denotes the value of the probability density function (pdf) at the rain rate R. The approaches of Doneaud et al (1981) and Atlas et al (1990) obviously assume that S(t) is constant for a given threshold t, that is, the theory relies on the existence of a well-behaved pdf of the rain rate either of a single storm during its…”
Section: Basicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a relationship, often seen in rainfall observations (Doneaud et al, 1981;Kedem and Pavlopoulos, 1991), is not explicitly defined within the TAM-SIM model. It can therefore be used as a further test of the ability of TAMSIM to reproduce the observed rainfall spatial structure (Onibon et al, 2004).…”
Section: Validation Of the Modelmentioning
confidence: 96%
“…Since the time when digital radar data of high accuracy have become readily available -roughly 1975 -great attention has been devoted to new techniques such as Doppler and depolarization measurements but very little work has been carried out on integrated storm properties. Exceptions are certain studies motivated by the needs of hydrology, of which the research of Doneaud et al (1981) is a good example, and work by Rogers et al (1983) on the sizes and internal structure of individual rainshowers. Although these studies are related to the question of precipitation development, they do not face the question directly.…”
Section: Introductionmentioning
confidence: 97%